Edukasi dan Pelatihan Pengolahan Tanaman Obat Untuk Menunjang Kesehatan Masyarakat Kelurahan Angke - Meiyanti; Yohana; Eveline Margo; Erlani Kartadinata; Juni Chudri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The utilization of traditional medicine derived from nature has increased its use in recent years, this is in line with the current trend of returning to nature. The use of traditional medicine in the form of herbal medicine has been done since ancient times and has been passed down from generation to generation. However, the use of TOGA as medicine is still low in prevalence, especially in the DKI Jakarta area according to 2018 Riskesdas data. The level of knowledge is one of the factors associated with the utilization of herbal medicine. Limited knowledge about medicinal plants and how to process and make herbal medicines properly and correctly becomes an obstacle to utilization. Various benefits can be obtained from the utilization of TOGA both in terms of benefits, safety, and economic aspects, especially for community groups with economic limitations. This community service activity is carried out by providing education on useful medicinal plants, and plant parts that can be used as medicines and training on processing medicinal plants using household appliances. The purpose of this activity is to increase knowledge, utilization, and interest in processing medicinal plants.